THE CHALLENGES FOR THE IMPLEMENTATION OF FULL-TIME EDUCATION DURING THE COVID-19 PANDEMIC IN THE STATE OF AMAZONAS - Guerreiro Reis, Lenilda Molina; Cavalcante Franca, Rosangela de Fatima [UNESP] (Fundacao Univ Tocantins, 2022)
This is a qualitative exploratory-descriptive research, supported by the content analysis proposed by Bardin (2011), carried out through individual online meetings, via Google Meet, held from 01 to 09 June 2021, in which seven teachers who work in high school at the school in question answered a semi-structured and recorded interview. The data obtained were organized in the Analysis Category created a priori, namely: Challenges for the implementation of training contents in the pedagogical practice of teachers. The results show that the challenges that make it difficult to materialize content in pedagogical practice concern the lack of preparation of teachers to work on digital platforms of online classes, the financial conditions of students, making access to classes difficult, the physical infrastructure of the school, the lack of teaching and teaching materials and the problem of teachers who are not permanent.
Keywords: Continuing Education; Integral Education; Pedagogical Practice; Amazonas